Paving Block Investigation Using Waste Plastic, Used Oil, And Styrofoam with Different Variables - St. Nugroho Kristono; Muhammad Malik Arifandi; Yudi Dermawan; Istianto Budhi Rahardja; Ahmad Mahfud (Journal of Applied Sciences and Advanced Technology, 2021)
Paving block is a composition of building materials made from a mixture of portlandcement or similar hydraulic adhesives, which are components of building materials that are very commonly used. But besides that, the dependence on the use of cement as an adhesive for Paving Blocks is still high. Therefore, the solution taken is to use waste plastic, Styrofoam, and used oil as materials for making Paving Blocks. Based on the results of data processing, it can be concluded that the manufacture of paving blocks using a mixture of plastic, used oil, and styrofoam has several stages, namely the stages of preparing tools and materials, taking and collecting plastic waste, used oil , and styrofoam, heating stages, mixing stages, the printing stage, the release stage and the drying stage, and the laboratory testing stage. This study uses 6 comparisons of mixed materials. The results of the trial of making paving blocks using a good mixture of plastic waste and used oil, namely with a composition of 67%: 33% with an average compressive strength of 63.2 MPa and water absorption capacity of 2.4% entered into quality A used for roads while paving blocks with plastic waste materials, used oil, and styrofoam have the best compressive strength value, which is 26.0 MPa with a composition of 40%:50%:10% and the absorption power obtained is 5.2%. B quality is used for parking lots.